2019
DOI: 10.5603/fm.a2018.0088
|View full text |Cite
|
Sign up to set email alerts
|

Greater palatine foramen: assessment with palatal index, shape, number and gender

Abstract: Background: Accurate knowledge of location and relation with different parameters of the greater palatine foramen (GPF) is a crucial necessity in performing a variety of anaesthesiological, dental and surgical procedures. The main aim of this study was to identify the GPF's locations, numbers and shapes via associating with gender and palatal indices and compare with literature results. Materials and methods: This study was held on the cranium collections of the many anatomy departments in Turkey. Various metr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…But at the same time it is also important to locate it precisely to perform the maxillary nerve block to achieve the profound anaesthesiaof hemi maxilla [6]. The importance of GPF is not only confined to the successful outcome of oral and maxillofacial surgeries, it is also reported that stimulation of pterygopalatine ganglion through this foramen is utilized for relieving the effects of paralysis in paralytic patients and also for patient interventions in cases of cerebral vasospasmor cluster and migraine headache [7]. Standard text book of anatomy and anesthesiology mention the location of GPF as behind or posterolateral to the alveolar process of maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…But at the same time it is also important to locate it precisely to perform the maxillary nerve block to achieve the profound anaesthesiaof hemi maxilla [6]. The importance of GPF is not only confined to the successful outcome of oral and maxillofacial surgeries, it is also reported that stimulation of pterygopalatine ganglion through this foramen is utilized for relieving the effects of paralysis in paralytic patients and also for patient interventions in cases of cerebral vasospasmor cluster and migraine headache [7]. Standard text book of anatomy and anesthesiology mention the location of GPF as behind or posterolateral to the alveolar process of maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies investigated neurovascular structures in the anterior maxilla which may show different variations. Greater palatine canal and Nasopalatine canal are from those structures [21,28,[34][35][36][37]. Variants such as accessory canal of canalis spinuosus was studied by many investigators.…”
Section: Introductionmentioning
confidence: 99%
“…In the posterior region of the hard palate, the greater palatine and lesser palatine canals and foramina were studied for their anatomical features [18,28,34,36]. The greater palatine nerve canal as an important maxillary anatomical landmark is located bilaterally.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the meta-analysis regarding the distance between the greater palatine foramen and surrounding anatomical landmarks are presented in Table 4 . A total of 8 studies [ 8 , 11 , 29 , 35 , 56 , 63 , 77 , 83 ] ( n = 2358 subjects) reported data on the distance from the greater palatine foramen to the posterior nasal spine (GPF–PNS). The pooled mean, across the eight studies, was calculated to be 17.21 mm (95% CI = 16.34–18.09 mm).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 38 studies [ 1 , 5 , 7 , 8 , 10 , 11 , 16 , 19 – 22 , 27 , 29 , 36 – 38 , 40 45 , 48 , 56 59 , 63 , 65 , 66 , 73 , 77 , 80 – 85 ] ( n = 5479 subjects) reported data on the distance from the greater palatine foramen to the median maxillary suture (GPF–MMS). The pooled mean, across the 38 studies, was calculated to be 15.22 mm (95% CI = 15.00–15.43 mm).…”
Section: Resultsmentioning
confidence: 99%